The Synesthesia in John Keats' Ode - Martina Girsang; Mega Patrisia Manalu; Rainy Agria Agnes; Rifkha Sinambela; Prity Cecilia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Poetic synaesthesia is frequently used in poetry, and it can be thought of as a type of poetic metaphor. Synaesthesia can be defined as the human capacity to comprehend the objective world from a cognitive point of view. A tried and true method for generating circles and expressing ideas. Synaesthesia is used by people who create works of literature, particularly poetry, as a means of expressing the feelings and experiences that are unique to them. Synaesthesia is a manifestation of the rich creativity and imagination that people possess. The purpose of this paper is to clarify, from a cognitive point of view, the characteristics of synaesthesia as well as the powerful effect that synaesthesia has on the emotional expression of literary creators through an analysis of Keats' ode. This will allow readers to better understand the emotions that literary creators feel and to feel literary works more profoundly.Keywords: Poetry; Synaesthesia; Cognition; John Keats; Ode